If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + -2 = -2 Reorder the terms: -2 + d = -2 Add '2' to each side of the equation. -2 + 2 + d = -2 + 2 Combine like terms: -2 + 2 = 0 0 + d = -2 + 2 d = -2 + 2 Combine like terms: -2 + 2 = 0 d = 0 Solving d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Simplifying d = 0
| 7e+12=4c+78 | | 4x+3x+1-3x-7+x= | | x-1=4(x+2)-5(x+1) | | x-1=4(x+2)-5 | | 6c+3= | | 3e^5x-2=3 | | -3x-5(4x+8)=-17 | | 2(x-3)=5(x+2)-1 | | 5x^2-12x=9 | | y/4+3=8 | | 5x^2-12x=-3 | | 61=6-8x-38 | | 4n+4n+1-7n-2n-6= | | 5x^2-12x=7 | | -7m+9(2m-3)= | | 18(b-1)+2=2(9b-8) | | 2(x-4)=x(2+1) | | 3x^3+3x^2+4x+4=0 | | 2x=x+5 | | 2x^3+11x^2-16x+5=0 | | 9=-3x+45 | | 7(x+6)=7x-6 | | 6-4r-5r-1= | | -35-3x=5(2x-3)+6 | | 4a+7=3a+18 | | 8x-9=22 | | 3(2y-5)-y=6 | | 12t+2+7t+5= | | 11m-13=12m+14 | | 9m-7=9+m | | 14x-11-3x=3 | | 9x-8=4x+12 |